El espejo de agua de la laguna de cochapamba como fuente del desarrollo económico y turístico de la parroquia del valle, cantón Cuenca - Peralta Vásquez, Carlos Alberto (2010)
This document arises from the lack of initiative of the local authorities and the population itself, to recover an element that claims to be an icon in the parish of El Valle, which for a long time has been anonymous for some time and such anonymity has caused the lagoon and its immediate area of ​​influence is in an abandonment that has caused much deterioration to this ecosystem. So it is necessary and essential to make a proposal alternative that manages to rescue this lake wetland and prevent it from continue deterioration. To achieve this rescue it is necessary carry out certain activities that contribute to rescuing this ecosystem that at the moment is vulnerable. In the strategies that are proposed for the elaboration of this management and recovery of the lake wetland consist of awareness and development of campaigns in favor of care and defense lake wetland. Another strategy on which the plan and its success depend is to control the water quality of the lagoon or constant monitoring of the same, in where we mention the removal of cattails and dredging to recover its flow of waters. Urban design and the design of architectural elements is another fundamental strategy to improve the lagoon and its area of ​​influence immediate, with which we will create an alternative tourism, experiential and tourism green or ecotourism. For the execution of the strategies it has to go hand in hand with the Institutional strengthening, to contribute with the administrative, which it leads to empowerment by local authorities. ........................................